Topological stability for fuzzy expansive maps - Badilla L. (2021)
The authors would like to thank Carlos A. Morales, for useful talks on the subject of expansiveness and shadowing. Also, the authors would like to thank Professor H. Miranda and the anonymous reviewers for their valuable comments that helped to improve the final version of the article. The first author was partially supported by CONICYT PFCHA/DOCTORADO NACIONAL/2017-21170110 and Agencia Nacional de Investigaci?n y Desarrollo-ANID, Chile, project FONDECYT 1181061. The second author was partially supported by Agencia Nacional de Investigaci?n y Desarrollo-ANID, Chile, project FONDECYT 1181061, by Universidad del B?o-B?o, Chile, project 196108 GI/C, and by Programa do Postdoutorado Ver?o 2017-2019, IMPA, Rio de Janeiro, Brasil. The last author was partially supported by FONDECYT (Per?) contract 100?2018.